The Role of Organizational Commitment in Mediating the Influence of the Physical Work Environment and Organizational Culture on the Performance of Perumda Pasar Argha Nayottama Employees, Buleleng District - KURNIANINGSIH, M Retno Prima; MARTADIANI, A.A. Media; DHARMANEGARA, Ida Bagus Agung (International Journal of Environmental, Sustainability, and Social Science, 2024)
Employee performance plays a very important role in the success of a company. Good company performance is reflected in the superior and dedicated performance of employees. On the other hand, poor performance reflects declining company performance. To find out the factors that cause a decline in performance, it is necessary to conduct research, especially at Perumda Pasar Argha Nayottama which is experiencing the phenomenon of not achieving company performance in 2022. The aim of this research is to analyze the influence of the physical work environment and organizational culture on employee performance with organizational commitment as a mediating variable in Perumda Pasar Argha Nayottama, Buleleng Regency. The number of samples used was 72 employees from a total population of 258 employees, with a sampling technique using the Slovin formula. The data analysis used in this research is SEM-PLS inferential analysis. The results of this research indicate that the physical work environment has a positive and significant effect on employee performance. Physical Work Environment has a positive and significant effect on Organizational Commitment. Organizational culture has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on organizational commitment. Organizational Commitment has a positive and significant effect on Employee Performance. The Physical Work Environment has a positive but not significant effect on Employee Performance through Organizational Commitment, this means that Organizational Commitment is not able to mediate (Ummediated). Organizational culture has a positive and significant effect on employee performance through organizational commitment, partial mediation.